ChemInform Abstract: An FeF3·0.5H2O Polytype: A Microporous Framework Compound with Intersecting Tunnels for Li and Na Batteries. Issue 46 (24th October 2013) - Li, Chilin; Yin, Congling; Gu, Lin; Dinnebier, Robert E.; Mu, Xiaoke; van Aken, Peter A.; Maier, Joachim
Abstract A new open‐framework fluoride pyrochlore phase, FeF3·0.5H2O, is prepared from a mixture of Fe(NO3)3·9H2O and single‐wall carbon nanotubes suspended in [bmim]BF4 or 1‐decyl‐3‐methylimidazolium tetrafluoroborate (100 °C, 12 h).